Data for the paper "Molecular dynamics simulation of the elliptical vibration assisted machining (EVAM) of pure iron" - Goel, Saurav; Duarte Martinez, Fabian; Giusca, Claudiu (Cranfield University, 2018)
Data files used for figures 3 and 5 in the associated article from the Journal of Micromanufacturing. These need to be opened in the Origin software (https://www.originlab.com/).
Keywords: 'MD simulation'; 'elliptical machining'; 'pure iron'; 'tool wear'; 'Machining'; 'Manufacturing Processes and Technologies (excl. Textiles)'